2022
DOI: 10.1115/1.4053749
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Human Synovial Fluid From Osteoarthritis Patients and Healthy Individuals on Lymphatic Contractile Activity

Abstract: The lymphatic system has been proposed to play a crucial role in preventing the development and progression of osteoarthritis (OA). As OA develops and progresses, inflammatory cytokines and degradation by-products of joint tissues build up in the synovial fluid (SF) providing a feedback system to exacerbate disease. The lymphatic system plays a critical role in resolving inflammation and maintaining joint homeostasis, however, there is evidence that the lymphatics can become dysfunctional during OA. We hypothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 96 publications
0
2
0
Order By: Relevance
“…They also showed that MetSyn conditions diminish eNOS expression, thereby affecting the flow‐mediated changes in lymphatic function 71 . Michalaki et al 72 used rat isolated contracting collecting vessels to reveal the effect of osteoarthritis, a condition that leads to inflammation, on lymphatic contractile activity, and showed that the pumping function of the lymphatic vessel draining the joint can be significantly compromised in osteoarthritis leading to the possibility of investigating novel therapeutics. Also, connecting canulated popliteal lymph vessels from TNF‐transgenic mice to a wide range of hydrostatic pressures showed that inflammatory arthritis significantly reduces pumping amplitude, ejection fraction, and fractional pump flow 49 .…”
Section: Ex Vivo Modelsmentioning
confidence: 99%
“…They also showed that MetSyn conditions diminish eNOS expression, thereby affecting the flow‐mediated changes in lymphatic function 71 . Michalaki et al 72 used rat isolated contracting collecting vessels to reveal the effect of osteoarthritis, a condition that leads to inflammation, on lymphatic contractile activity, and showed that the pumping function of the lymphatic vessel draining the joint can be significantly compromised in osteoarthritis leading to the possibility of investigating novel therapeutics. Also, connecting canulated popliteal lymph vessels from TNF‐transgenic mice to a wide range of hydrostatic pressures showed that inflammatory arthritis significantly reduces pumping amplitude, ejection fraction, and fractional pump flow 49 .…”
Section: Ex Vivo Modelsmentioning
confidence: 99%
“…Additionally, there is a negative correlation between lymphatic vessel density and synovial effusion, which is a characteristic feature of advanced stages of OA development 50 . The reduced lymphatic vessel density may contribute to the retention of synovial fluid in OA patients, potentially exacerbating joint inflammation by impairing lymphatic pumping function 116 . In addition to the number of lymphatic vessels, the relationship between the severity of OA and the number, size, and central fatty changes of DLNs observed in MR images of patients does not exhibit a linear trend 117 .…”
Section: Introductionmentioning
confidence: 99%